ТЕАТРАЛЬНОЕ МАСТЕРСТВО КАК ОДИН ИЗ СПОСОБОВ ПОВЫШЕНИЯ ВОСПИТАТЕЛЬНОГО ПОТЕНЦИАЛА СТУДЕНТОВ ПЕДАГОГИЧЕСКИХ КОЛЛЕДЖЕЙ - Шалапина, О.Б.; Калинина, А.А. (My University, 2019)
Аннотация Статья посвящена таким актуальным вопросам, как затруднения, связанные с живым общением, и снижение культуры речи у студентов педагогических колледжей. Цель данной статьи – поделиться опытом решения данной проблемы. Abstract The article is dedicated to such actual questions as difficulties, connected with the live communication and reduction of the speech culture of students of pedagogical colleges. The aim of the article is to share our experience of solving this problem.
Theatrical skills as one of the ways of improving the educational potential of students of pedagogical colleges
Keywords: воспитание личности; образование; воспитание; профессионализм; студент; personality education; education; upbringing; professionalism; student